EVALUASI KETERGUNAAN WEBSITE PERPUSTAKAAN UNIVERSITAS KRISTEN SATYA WACANA DENGAN MENGGUNAKAN METODE SYSTEM USABILITY SCALE - Herdin Yohnes Madawara; Danny Manongga; Hendry Hendry (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
This research was conducted with the aim of evaluating the usability of the Satya Wacana Christian University (UKSW) Library website using the System Usability Scale (SUS) method. This research also aims to identify areas that need to be improved in the UKSW Library website. Respondents in this study were UKSW students who had used the library website. This study used the SUS questionnaire consisting of 10 questions with a 5-point Likert scale. The results of the SUS calculation show that the average value of the usability of the UKSW Library website is 59.514, which is in the medium or "OK" category. Further analysis shows that areas that need to be improved are clarity of information, ease of navigation, and visual appearance. This research is expected to provide input for the UKSW Library in developing the website in order to increase usability and meet the needs of its users. The conclusion of this research is that the UKSW Library website still has some areas that need to be improved to increase usability.